The Implementation of Good Corporate Governance on Employee Compliance at PT. Sri Pamela Medika Nusantara in Tebing Tinggi City - Dina Mariana; Ginting, Budiman; Aflah (Mahadi: Indonesia Journal of Law, 2025)
This study aims to examine the effect of the implementation of Good Corporate Governance (GCG) on employee compliance at PT. Sri Pamela Medika Nusantara in Tebing Tinggi. The application of GCG principles is considered crucial in enhancing the efficiency and effectiveness of company operations, particularly in the healthcare sector, which requires high ethical and professional standards. This research was conducted using a juridical-empirical approach with a descriptive-analytical method. Data for this study was obtained through interviews, literature studies, documentation, and the distribution of questionnaires. The collected data were then analyzed using a qualitative descriptive approach. The results of this study indicate that the application of GCG principles at PT. Sri Pamela Medika Nusantara has a significant impact on employee compliance. Supporting factors include a strong understanding of GCG principles, such as transparency, accountability, and fairness, which have been shown to encourage employees to comply with company policies. The commitment of the company’s management also plays a vital role in creating a work environment that supports the optimal implementation of GCG. However, inhibiting factors that may reduce the effectiveness of GCG implementation, such as employees’ lack of knowledge about applicable regulations and the company’s work culture not fully supporting GCG principles, were also identified. Moreover, non-compliance with GCG principles can have negative consequences for the company, both in terms of reputation and legal aspects. Ongoing non-compliance could lead to legal actions, including employee termination or more severe sanctions, which may affect the company’s sustainability and performance.